Cdc48: A Swiss Army Knife of Cell Biology. (15th September 2013) - Baek, Guem Hee; Cheng, Haili; Choe, Vitnary; Bao, Xin; Shao, Jia; Luo, Shiwen; Rao, Hai
Abstract : Cdc48 (also called VCP and p97) is an abundant protein that plays essential regulatory functions in a broad array of cellular processes. Working with various cofactors, Cdc48 utilizes its ATPase activity to promote the assembly and disassembly of protein complexes. Here, we review key biological functions and regulation of Cdc48 in ubiquitin-related events. Given the broad employment of Cdc48 in cell biology and its intimate ties to human diseases (e.g., amyotrophic lateral sclerosis), studies of Cdc48 will bring significant insights into the mechanism and function of ubiquitin in health and diseases.